High pressure Raman study of layered Mo0.5W0.5S2 ternary compound. (30th March 2016) - Kim, Joon-Seok; Moran, Samuel T; Nayak, Avinash P; Pedahzur, Shahar; Ruiz, Itzel; Ponce, Gabriela; Rodriguez, Daniela; Henny, Joanna; Liu, Jin; Lin, Jung-Fu; Akinwande, Deji
Abstract: Ternary two-dimensional (2D) transition metal dichalcogenide compounds exhibit a tunable electronic structure allowing for control of the interlayer and the intralayer atomic displacement to efficiently tune their physical and electronic properties. Using a diamond anvil cell, hydrostatic pressure was applied to Mo0.5 W0.5 S2 up to 40 GPa in order to study the optical phonon vibrational modes. Analysis of the high-pressure Raman spectra shows that the two in-plane E2g modes resembling that of pristine MoS2 and WS2, as well as disorder-activated longitudinal acoustic phonon mode, are hardened and suppressed as pressure increases. The two A1g modes of the ternary compound that resemble the A1g modes of pristine MoS2 and WS2, displayed similar Raman shifts to the pristine compounds as pressure increases. A Raman peak at 470 cm −1 that is close to A1g peaks emerges at ∼8 GPa, which represents a disorder-activated pressure-induced out-of-plane Raman mode observed only in the ternary compound under high pressure. At pressures above ∼30 GPa, a Raman peak at approximately 340 cm −1 is observed, signifying additional disorder-activated vibration mode. Our results reveal the enhanced interactions in the structural and vibrational behavior of the MoS2 and WS2 domains in the Mo0.5 W0.5 S2 compound under hydrostatic pressure. These results could have implications in understanding the electronic, optical, and structural properties of the new 2D ternary compound materials under extreme mechanical conditions.